Synthesis and conformational study of chiral oxepines: the baylis-hillman reaction and RCM approach with sugar aldehyde - Jadhav, Vrushali H.; Bande, Omprakash P.; Pinjari, Rahul V.; Gejji, Shridhar P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2009)
The Baylis-Hillman reaction of 3-O-allyl-alpha-D-xylo-pentodialdo-1,4-furanose 3 afforded a diastereomeric mixture of D-gluco- and L-ido-configured alpha-methylene-beta-hydroxy esters 4a and 4b, respectively, in a ratio of 2:3. Reduction of the ester functionality in 4a/4b gave alcohols 5a/5b. The diene thus formed in 5a/5b was subjected to ring-closing metathesis (Grubbs' second-generation catalyst) to afford oxa-bicyclic ring system 6a/6b in high yield. Further manipulation of the aectonide functionality in 6a and 6b afforded new polyhydroxylated oxepines 1a/2a and 1b/2b, respectively. The (1)H NMR of oxepines 1a and 1b in D(2)O showed doubling of signals indicating their existence in two different rotamers/conformers. This fact was substantiated by calculating energetics of 1 and 2 conformers using the density functional theory and correlating the calculated (1)H NMR chemical shift pattern with that of the experimental spectra.

Synthesis, electronic structure, DNA and protein binding, DNA cleavage, and anticancer activity of fluorophore-labeled copper(II) complexes - Bhat, Satish S.; Kumbhar, Anupa A.; Heptullah, Hussain; Khan, Ayesha A.; Gobre, Vivekanand V.; Gejji, Shridhar P.; Puranik, Vedavati G. (Inorganic Chemistry, 2011)
Two mononuclear fluorophore-labeled copper(II) complexes [Cu(nip)(acac)](+) (2) and [Cu(nip)(2)](2+) (3), where fluorophore is 2-(naphthalen-1-yl)-1H-imidazo[4,5-f][1,10]phenanthroline (nip) (1) and acac is acetylacetone, have been synthesized aid characterized by various techniques. The ligand 1 and complex 2 are structurally characterized by single-crystal X-ray diffraction. The coordination geometries around the copper are square planar in solid as well as solution state as evidenced by electron paramagnetic resonance (EPR) spectroscopy. The density functional calculations carried out on 1-3 have shown that electron-rich regions in the highest occupied orbital are localized on the naphthalene end partly on the phenanthroline moiety. Both complexes 2 and 3 in dimethyl sulfoxide (DMSO) exhibit near square planar structure around the metal ion in their ground state. Time-dependent density functional theory (TD-DFT) calculations reveal that Cu(II) ion in complex 2 shows tetrahedral coordination around the metal while 3 retains its square planar geometry in the lowest excited state. The interaction of complexes with calf-thymus DNA (CT DNA) has been explored by using absorption, emission, thermal denaturation, and viscosity studies, and the intercalating mode of DNA binding has been proposed. The complexes cleave DNA oxidatively without any exogenous additives. The protein binding ability has been monitored by quenching of tryptophan emission in the presence of complexes using bovine serum albumin (BSA) as model protein. The compounds showed dynamic quenching behavior. Further, the anticancer activity of the complexes on MCF-7 (human breast cancer), HeLa (human cervical cancer), HL-60 (human promyelocytic leukemia), and MCF-12A (normal epithelial) cell lines has been studied. It has been observed that 3 exhibits higher cytotoxicity than 2, and the cells undergo apoptotic cell death.

Synthesis and biological activity of imidazole based 1,4-naphthoquinones - Choudhari, Dinkar; Salunke-Gawali, Sunita; Chakravarty, Debamitra; Shaikh, Samir R.; Lande, Dipali N.; Gejji, Shridhar P.; Rao, Pradeep Kumar; Satpute, Surekha; Puranik, Vedavati G.; Gonnade, Rajesh (New Journal of Chemistry, 2020)
Design and development of drugs in multi-drug resistant (MDR) infections have been of growing interest. We report the syntheses, and antibacterial and antifungal activities of imidazole-based 1,4-naphthoquinones (I-1 to I-4; 1-alkyl-2-methyl-1H-naphtho[2,3-d]imidazole-4,9-dione (alkyl = methyl to butyl)) and their precursors (B-3; N-(3-chloro-1,-dioxo-1,4-dihydronaphthalen-2-yl)acetamide) and A-1 to A-4; N-(3-(alkylamino)-1,4-dioxo-1,4-dihydronaphthalen-2-yl)acetamide (alkyl = methyl to butyl). Crystal structures of B-3, A-1 to A-3 and I-2 to I-4 were obtained through single crystal X-ray diffraction experiments. Electronic structure and charge distribution have further been characterized with the use of Density Functional Theory. Seven of these derivatives display a broad spectrum of antibacterial activity against few selected bacterial strains (Gram-positive and Gram-negative). As demonstrated MIC values with B-2 and B-3 against bacterial isolates were 8-64 mu g ml(-1) and those against pathogenic yeast, C. albicans, were observed in the range of 128-256 mu g ml(-1). MIC data of these derivatives suggest them to be promising against pathogens.

Structural characterisation, anticancer properties, and BSA binding of 2,6-dipyrazinylpyridines: Insights from experiment and theory - Enumula, Sreenivasulu; Shaikh, Javed; Shaikh, Amin; Sheikh, Kounsar N.; Tambe, Pranav; Lande, Dipali N.; Gejji, Shridhar P.; Shaligram, Parth; Gonnade, Rajesh; Bhadbhade, Mohan; Ahmed, Khursheed (Journal of Molecular Structure, 2026)
The phenyl-(2,6-di-2-pyrazinyl)pyridine derivatives (L1, L2) were synthesized using a one-pot Krohnke-type method, starting from 2-acetylpyrazine and substituted benzaldehydes. Their structures were characterized using a combination of spectroscopic (NMR, HRMS) and single-crystal X-ray diffraction techniques, complemented by density functional theory (DFT). Single-crystal X-ray diffraction reveals that L1 crystallizes in the C2/c space group (T = 296 K) with its supramolecular assembly being stabilized by C-H & ctdot;N and pi-pi stacking interactions, whereas L2 facilitates C-H & ctdot;N, N-H & ctdot;pi bifurcated, and pi-pi* interactions. The bio-interaction properties of L1 were studied using fluorescence spectroscopy with bovine serum albumin (BSA) as a model protein. Fluorescence studies demonstrated L1 induces static quenching of BSA, with a binding constant of 5.15 x 104 mol & sdot;dm-3. Synchronous and three-dimensional fluorescence spectra further demonstrated that L1 brings forth significant conformational changes in BSA. The compounds were evaluated for cytotoxicity against the HCT-116 human colorectal cancer cell line.
Keywords: 2; 6-dipyrazinylpyridines; Bovine serum albumin interaction; Cytotoxicity (HCT-116 cells); Density functional theory; Halogenated derivatives; Single-crystal X-ray diffraction